MOBILE BASED USER INTERFACE / USER EXPERIENCE E-RAPOR DESIGN USING LEAN USER EXPERIENCE METHOD (CASE STUDY IN SMAN 4 PROBOLINGGO CITY) - Rahman Fadillah Sugandhi; Tan Amelia; Julianto Lemantara (Jurnal Sistem Informasi Universitas Dinamika, 2021)
E-Rapor is a web-based academic information system application from the Education Officewhich has been around since 2016 with the aim of providing academic information to students. In the web version of the E-Report Card, there is no notification when the value has been entered by teacher. Apart from the absence of an E-Report Card notification, the current web version still looks ambiguous causing reduced interest in using the web version of the E-Report Card application. With problems above, then in this study a prototype will be made on the E-Report card based application mobile which has been adapted for users who have busy activities later.